Robust atomic states for quantum information with continuous variables - Vudayagiri, Ashok; Sankhari, Bappaditya (Frontiers in Quantum Science and Technology, 2023)
Using a set of Zeeman sublevels of an Alkali atom such as Rubidium or Sodium, we propose to construct a pair of Coherent Population Trap (CPT) states, which can be individually addressed and populated at will. The system can be arranged such that there exists a dressed state which is a linear combination of these two CPT states. We have earlier shown capability of forming discrete Quantum Gates using this configuration (J.Phys. B, ( 2006), 39, 3919). In the present communication, we will show how the same configuration can be used to prepare and operate continuously varying state. The state can be mapped to a 2D parametric space in such a way that any desired vector within it can be prepared and also a continuous, adiabatic evolution from one vector to other is possible. A method to exploit a continuous interaction potential is also suggested, which can be used in quantum computation. We discuss how a continuous variable quantum computation can be performed using such states.